The use of early-grade reading benchmarks to improve the efficacy of assessment in African languages - Lobelo, Asanda (School of Economics, 2025)
South Africa is facing a ‘reading crisis' where the majority of learners are unable to read for meaning or with understanding by the end of Grade 4. In recognizing this crisis, there have been considerable sector-wide efforts to improve foundational literacy outcomes, including the establishment of reading benchmarks in African languages. These benchmarks are a measure of grade-level reading proficiency that can be used to monitor progress at the national, provincial, district and school level. One way the benchmarks could be used productively at the classroom level, is enabling teachers to interpret assessment results into learning levels, based on progress towards meeting the benchmark. Formative assessment is crucial for effective teaching and implementing the curriculum. Furthermore, differentiated instruction programs have been gaining traction for their demonstrated potential to improve learning outcomes in contexts where within-grade heterogeneity is high with many learners not keeping pace with the curriculum. A key assumption of these programs is that educators know the learning levels of their learners. The evidence around teacher formative assessment practices and the efficacy thereof suggests that this assumption is not likely to hold in the South African context. To create a basis for differentiated instruction programs to improve literacy outcomes, teacher knowledge of the learning levels of their learners needs to be evaluated. Secondly, the processes through which teachers gain that knowledge, the formative assessment process, needs to be strengthened. The overarching purpose of this study is to generate insights into how the newly established benchmarks could be productively used in South African classrooms. We do this by examining current teacher knowledge of learning levels through their existing formative assessment practices and evaluate the effectiveness of a benchmarks-orientated intervention in improving that knowledge. Using longitudinal data from this pilot study across 39 schools, this paper estimates the intent-to-treat (ITT) effect, local average treatment effect and average treatment effect on the treated (ATT) of the intervention. The results show that teachers tend to overestimate the performance of their learners across the achievement distribution and the size of the misestimation is relatively large. Take-up rates of the intervention were fairly low and variable, but we find evidence that the intervention improved knowledge of relative reading proficiency of intervention-trained teachers relative to their untrained counterparts. This is even more so for trained teachers for whom we are able to confirm use of the intervention materials. These findings underscore the importance of enhancing the resources, training, and support provided to teachers for the formative assessment process. Furthermore, the inclusion of the reading benchmarks could be useful in augmenting such support.